KINERJA PEMERINTAHAN DESA DALAM PELAYANAN PUBLIK DI BIDANG KEPENDUDUKAN : STUDI DESA GEMPOL SARU KECAMATAN SEPATAN TIMUR KABUPATEN TANGERANG - Miftahul Hazami; Doddy Mulyono (Gapenas Publisher, 2023)
The formulation of the problem in this research is: How does the Gempol Sari village government perform in providing public services in the field of population and apart from that, what are the forms of service? This research uses a descriptive research method using a qualitative approach with the aim of finding, conceptualizing and describing events. -events that occur at the research location and build and discover new theories related to the research matter. The focus of this research is the Government's performance in providing public services and the forms of population services provided by village officials to the community. The results of the research show that the performance of the Gempol Sari village government in providing services to the community is considered quite good, this is reflected in the ability to carry out their duties and responsibilities as community servants, the work enthusiasm possessed by Gempol Sari village officials in carrying out their responsibilities, with attitudes such as The village government is able to provide a service of sufficient quality to the community. It's just that the level of discipline of Gempol Sari village officials is considered to be still lacking, thus becoming an obstacle to the service process. The performance of the village government in providing services in the population sector is seen from the process of implementing services such as procedures or procedures, timeliness and the amount of costs incurred by the community to obtain a service in the population sector which is considered very good. This is reflected in all implementation mechanisms that meet the specified criteria. such as the presence of elements of clarity and certainty, openness, efficiency and economy. The forms of services in the field of population that are often provided by the Gempol Sari village government include administrative ones which include fulfilling personal identity documents, as well as certificates relating to other population issues